2016
DOI: 10.3892/mmr.2016.5552
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of ING4 and P53 enhances hypopharyngeal cancer chemosensitivity to cisplatin in vivo

Abstract: Hypopharyngeal cancer is a distinct type of malignant head and neck tumor, which exhibits low sensitivity to anti-cancer drugs. The importance of developing methods for reducing chemotherapy resistance, and improving and enhancing prognosis has previously been emphasized and is considered a challenge for effective clinical treatment of hypopharyngeal cancer. The current study investigated the effects of co-expression of inhibitor of growth protein 4 (ING4) and P53, a tumor suppressor gene, on chemosensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In specific, the combination therapy induced more robust activation and infiltration of NK cells, induction of apoptosis, and inhibition of angiogenesis and vascularization than monotherapy in vivo ( Figures 5 and 6 ). These in vivo findings support the previously published considerations that concomitant delivery of ING4 gene, 19 , 20 , 25 and likewise TRAIL gene, 8 , 10 , 13 , 14 with another potential tumoricidal gene is more effective in gene-based cancer therapy to overcome cancer resistance, and also re-highlight the importance of OAd in mediating potential cancer-targeting dual gene virotherapy strategy and providing a more meaningful therapeutic maneuver against multi-genic and highly resistant cancers, such as HCC, particularly if the two transgenes are well chosen. 7 , 8 , 9 , 10 , 11 As combination of two viruses is a major challenge for translation relevance compared with use of single virus, a future study should examine a single oncolytic virus co-expressing both TRAIL and ING4 genes to examine whether expression of both genes by a single vector system can still elicit more potent anticancer effect than a control vector expressing single therapeutic gene.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In specific, the combination therapy induced more robust activation and infiltration of NK cells, induction of apoptosis, and inhibition of angiogenesis and vascularization than monotherapy in vivo ( Figures 5 and 6 ). These in vivo findings support the previously published considerations that concomitant delivery of ING4 gene, 19 , 20 , 25 and likewise TRAIL gene, 8 , 10 , 13 , 14 with another potential tumoricidal gene is more effective in gene-based cancer therapy to overcome cancer resistance, and also re-highlight the importance of OAd in mediating potential cancer-targeting dual gene virotherapy strategy and providing a more meaningful therapeutic maneuver against multi-genic and highly resistant cancers, such as HCC, particularly if the two transgenes are well chosen. 7 , 8 , 9 , 10 , 11 As combination of two viruses is a major challenge for translation relevance compared with use of single virus, a future study should examine a single oncolytic virus co-expressing both TRAIL and ING4 genes to examine whether expression of both genes by a single vector system can still elicit more potent anticancer effect than a control vector expressing single therapeutic gene.…”
Section: Discussionsupporting
confidence: 91%
“… 3 , 4 , 5 , 6 , 7 ING4 has been lately identified as a potential candidate in gene-based cancer therapy to halt tumor growth and angiogenesis and to facilitate antitumor apoptosis, particularly when combined with additional anticancer gene or drugs. 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 In despite of this, its beneficial role in OAd-based cancer gene virotherapy is not well investigated yet and remains to be determined. Likewise, to the best of our knowledge there is no previous attention has been given to the potentiality of combining TRAIL; a potent antitumor apoptotic ligand that its importance in cancer combination therapies has been strongly recommended, 8 , 10 , 14 with ING4 to improve their overall anticancer response and overcome cancer resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, p53 gene‐targeted mutations can knock out the p53 gene in rat embryonic stem (ES) cell chimeras in the ES cell genome [17]. As a transcription factor, p53 is the first member of the p53 family, eliciting genome maintenance by regulating cell cycle arrest, DNA repair, senescence and apoptosis occurring in response to a broad range of cellular stresses [18,19]. It has been reported that the survival of tumor cells lacking functional p53 is increased due to decreased apoptosis in these cells [20].…”
Section: Introductionmentioning
confidence: 99%